RELASI TRADISI MUSLIM JAWA DAN MUSLIM BERBER (Tinjauan Atas Kemiripan pada Penamaan Bulan-Bulan Islam Jawa Dan Berber Dalam Kaitannya Dengan Perayaan Hari-Hari Besar Islam) - Musonif, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
The relation between Javanese and Berber Islamic traditions can be seen from several Berber traditions such as religious holidays such as Mawlid, Eid al-Fitr and Eid al-Adha. The influence of Berbers is also seen in the names of Javanese Islamic months which have similar meanings to the names of Berber Islamic months. This relation can be traced to its historical roots from the pre-colonial period, precisely in the time of Wali Songo. There are some Islamic preachers in the past who came from the Maghrib (morocco) which is the residence of the Berbers. In addition Sultan Agung as the originator of the Javanese Islamic calendar based on his pedigree is also a descendant of the Maghrib. Keywords: Javanese Islamic Traditions, Berber Islamic Traditions, Islamic Month Relasi tradisi Islam Jawa dan Islam Berber dapat dilihat dari beberapa tradisi Berber Seperti perayaan hari besar agama misalnya Mawlid, Idul Fitri, dan Idul Adha. Pengaruh Berber juga tampak pada nama-nama bulan Islam Jawa yang secara makna memiliki kemiripan dengan nama-nama bulan Islam Berber. Relasi ini dapat dilacak akar sejarahnya dari masa pra kolonial, tepatnya pada masa wali songo. Ada beberapa tokoh juru dakwah Islam pada masa lalu berasal dari Maghrib (maroko) yang merupakan tempat tinggal orang-orang Berber. Selain itu Sultan Agung sebagai pencetus kalender Islam Jawa berdasarkan silsilahnya juga merupakan keturunan orang-Maghrib. Kata Kunci: Tradisi Islam Jawa, Tradisi Islam Berber, Bulan Islam